PROMOSI SEKOLAH SMK KARTIKA 1-1 PADANG MELALUI MEDIA GRAFIS (BOOKLET) - ARDI SETIAWAN, Drs. Nasbahri Couto, M.Sn, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Vocational high school (SMK) is a form of alternative education. School is SMK KARTIKA 1-1 Padang top schools that can directly work, concept school SMK KARTIKA 1-1 Padang is giving a special skill for each student depending majors, where each lesson is taught in detail from all the subjects thoroughly. Later SMK KARTIKA 1-1 Padang can pass the best graduates can directly work in their respective fields, are also concerned about the development of science which continues to grow rapidly. However, at present little is known about the advantages of vocational schools SMK KARTIKA 1-1 Padang because the promotion is done in less effective.Therefore, to introduce and promote schools SMK KARTIKA 1-1 Padang, needed a new design promotional media for vocational schools SMK KARTIKA 1-1 Padang, that will aim to introduce schools SMK KARTIKA 1-1 Padang this can be achieved to the target audience. For the design process begins with data collection, observation, interview and documentation. So the problems that occur in the promotion of vocational schools SMK KARTIKA 1-1 Padang can be seen, from the identification of the problem analyzed by using the theory of SWOT (strength or strength, weakness or weakness, opportunity or opportunities, threat or threats), with the understanding the entire information in a case .So the selection of more effective media campaign and the message to be conveyed to the target audience can be right on target. The design resulted in major media in the form of graphic media (booklets) which show how the state vocational schools SMK KARTIKA 1-1 Padang. The main promotional media features supporting media such as, billboards, banners, mini x-banners, posters, flyers, design clothing practice, member cards, brochures, ambush media (sticker blasting) and pin.Keywords : Kartika 1-1 SMK Padang, promotion, graphic media (booklets)